Responses of soil N-cycle enzyme activities to vegetation degradation in a wet meadow on the Qinghai-Tibet Plateau - Chang, Wenhua; Ma, Weiwei; Song, Liangcui; Tang, Yanmei; Long, Yongchun; Xu, Guorong; Yuan, Jianyu (Frontiers in Ecology and Evolution, 2023)
Soil enzymes play a vital role in the functioning of wetland ecosystems, driving energy flow and material cycling processes. Gahai wet meadow, one of the important components of alpine wetlands on the Qinghai-Tibet Plateau, has suffered serious degradation in the last 30 years due to climate change and human activities. We studied the spatial and temporal heterogeneity of soil nitrogen content and nitrogen (N)-cycle enzyme activities (i.e., urease, protease, nitrate reductase and nitrite reductase) in four degraded wet meadows in the Gahai wetlands. Our results suggested that with increasing wet meadow degradation, there was a significant decrease in soil water content, total nitrogen, ammonium nitrogen, microbial biomass nitrogen content, protease activities, and nitrite reductase activities; Conversely, soil temperature, nitrate nitrogen content, urease activities, and nitrate reductase activities increased significantly. Soil urease, protease, and nitrite reductase activities significantly decreased with increasing soil depth;The highest activity levels of the three N-cycle enzymes were observed in July and August. The linear mixed modeling results indicated that there were significant effects of degradation level and soil depth and their interactions on soil nitrate reductase and nitrite reductase activities (p < 0.01), while soil depth had significant effects only on soil urease and protease activities (p < 0.01). Redundancy analyses showed that soil ammonium and nitrate nitrogen were the main drivers of changes in soil N-cycle enzyme activity during the degradation of wet meadows. In summary, our study sheds light on the processes of soil enzyme activity in an alpine wetland ecosystem and provides valuable information for understanding the N cycling in these complex systems.